Evidence for shifting genetic structure among Caribbean giant barrel sponges in the Florida Keys - Deignan, Lindsey K. (2020)
The giant barrel sponge Xestospongia muta is a dominant member of Caribbean reef ecosystems. Populations of X. muta that have been monitored annually in plots on Conch and Pickles Reefs in the Florida Keys increased by as much as 122% between 2000 and 2012, raising questions about the processes structuring these growing populations. Microsatellite markers for the closely related Pacific giant barrel sponge X. testudinaria were optimized for X. muta using individuals from Conch and Pickles Reefs (located 5.5 km apart). Further, within one plot on Conch Reef (AQS3 − 20 m depth), each individual of X. muta was mapped and genotyped to investigate fine-scale spatial genetic structuring. Significant spatial autocorrelation was detected at 2-m distance, but the dispersal distance and neighborhood size could not be determined, suggesting that recruitment extends beyond the plot. Finally, sponge samples from Conch Reef (15- and 20-m depth) and Pickles Reefs (15-m depth) were pooled into a single population for Bayesian cluster analyses. Results showed two distinct genetic clusters in the population, Clusters 1 and 2, with a near absence of Cluster 2 sponges among the largest individuals. Comparisons of the microsatellite data with mortality and recruitment data obtained from the plots revealed that the shifting genetic structure is due to disproportionate reproduction or recruitment of Cluster 2 sponges. The selective forces responsible for this genetic shift remain unclear, but it is further evidence of the dramatic changes occurring on coral reefs in the Anthropocene.